In vivo antimicrobial effect of Camellia sinensis on oral bacteria - Moromi Nakata, Hilda (2007)
In order to determine, in vivo antimicrobial effect of Camellia sinensis infusión (green Tea), as a mouthwash at 10 %; not stimulated saliva of 32 seemingly healthy people was collected: 1) Before mouthwash, 2) immediately after, and 3) after 30 minutes. The samples were spread in Agar Tripticasa Soy Bean and Agar Mitis Salivarius Bacitracina; then proceeded to the recount of the forming units of colonies of Mutans Streptococci for mL: The statistical analysis of results, by means of “t” and Wilcoxon tests, indicate that significant differences exists. On the other hand in the analysis of the mouthwash to determine polyphenols presence, by means of the infrared spectrophotometry peaks transmitted in wave lengths for the oxydril groups (-0H) and aromatic ring were observed. One concludes that there is an effective reduction in the number of microorganisms of the mixed salivary micro flora, and in case of the amount of colonies of Mutans Streptococci, the decrease is significantly appreciated immediately later, maintaining the same significance in the 30 minute results.